High gain UWB horn antenna for concealed metal detection and microwave imaging application - Shaikh, Faraz Ahmed; Khan, Sheroz; Alam, A. H. M. Zahirul; Hassan Abdalla Hashim, Aisha; Badron, Khairayu; Yaacob, Mashkuri (Faculty of Natural Resources, University of Sindh, Jamsoro, Pakistan, 2018)
In this paper, the examination of recognition technology along with imaging system intended for the identification of metallic object inside or in the middle of two walls. The UWB frequency is used by ground–penetrating radar (GPR). The working mechanism of illuminating structure is centered on Time Domain Reflectrometry (TDR) by means of through wall imaging (TWMI). This paper describes an exceptional concept of recognition of barrier and distance between these barriers. The instrument Vector Network Analyzer (VNA) is used to produce very diminutive length pulses for to revealing the barrier, behind and between two barriers under examination with UWB probe antenna array system. The simulation outcomes of horn antenna have represented a massive potential for penetration in order to recognize a concealed metallic object positioned in the middle of two barriers and capable to estimate the gap width with well precision. Now it is considered to be an attractive expansion in the detection and imaging technology. For further improvement and to enhance the resolution of an image, improved quality filters have been industrialized.